The Role of Work Motivation as a Mediator in Enhancing Employee Performance in Village Financial Institutions, Badung, Bali - Yustina, Anak Agung Made Sintya; Gunadi, I Gst Ngr Bagus (International Journal of Scientific Research and Management (IJSRM), 2024)
Employee performance is one of the key factors that determines the success and sustainability of an organization. The research aims to find the influence of the physical work environment and situational leadership on employee performance with work motivation as a mediating variable in the LPD of Kerobokan Traditional Village, Badung Regency. The population and sample in this research were all LPD employees of Kerobokan Traditional Village, Badung Regency, totaling 42 people. Data collection was carried out using questionnaires, interviews, and documentation. Data analysis was carried out using path analysis. The results of the analysis show that the physical work environment has a positive effect on the work motivation of the LPD of the Kerobokan Traditional Village, Badung Regency, situational leadership on the work motivation of the LPD of the Kerobokan Traditional Village, Badung Regency, the physical work environment has a positive effect on the performance of the LPD employees of the Kerobokan Traditional Village, Badung Regency, leadership situational has a positive effect on the performance of LPD employees of Kerobokan Traditional Village, Badung Regency, work motivation has a positive effect on the performance of LPD employees of Kerobokan Traditional Village, Badung Regency. Work motivation can mediate the influence of the physical work environment and situational leadership on the performance of LPD employees in Kerobokan Traditional Village, Badung Regency.